Tolerância ao déficit hídrico de eventos de trigo transformados com o gene p5cs - Lima, Lettice Aparecida Dias Canete de (2010)
Wheat is one of the most important crops because the human diet is based on in many countries. The plant genetic transformation is considered an important tool in obtaining tolerant genotypes to abiotic stresses by the introduction of genes involved in mechanisms of cellular protection Proline is an osmoprotectant that can act in different mechanisms to increase the tolerance of plants. The enzyme ∆1-pyrroline-5-carboxylate synthetase (P5CS), encoded by the gene p5cs, is considered the limiting step in the proline biosynthesis. The study of the stability of transgene expression and productivity are critical to the commercial release of transgenic varieties. This study was conducted to evaluate five events through biophysical and production analysis under water stress. The results obtained were as the following parameters: relative water content (RWC); malondialdehyde contents (MDA), membrane stability index (%) and proline quantified. Production rates were quantified as the number of seeds per plant, number of ears per plant, 100 seeds average weight per plant and total weight of seeds per plant. The results permitted to conclude that transgenic plants responses were differently under severe and partial water stress conditions. Plants from different events under severe stress presented a higher content of proline (1.16x to 1.62x greater), lower levels of MDA and the IEMs were higher due to the fact of showing a more efficient mechanism of protection for cell membranes against oxidative stress. The perception of severe stress occurred at the 8th day of water restriction, however in partial water stress, the beginning of perception was after 12 days. The results obtained for production indexes were similar among events and stressed controls, which shows that, although there was expression of the transgene (p5cs) the higher amount of proline did not result in higher production of plants